Pengaruh Metode Latihan Drill Terhadap Kemampuan Gerakan Roll Depan Siswa Kelas VIII di SMP Negeri 18 Kota Bengkulu - Rahman, Taufik; Febrianti, Mariska; Anggara, Deffri (Educative Sportive, 2025)
This study aims to determine the effect of drill method training on the ability of floor gymnastics front roll. This research is a pre-experimental design which is a development of a two group pretest-posttest design. The sample in this study were students of class VIII 8 and VIII 9 SMP Negeri 18 Bengkulu City as many as 62 people. Which is given the treatment of each lesson from being given an initial test (pre test) and final data (post test). The initial test (pre test) obtained the highest score of 82, the lowest score of 50 and with an average score of 67.3 total score 2078. The final test (post test) with the highest score of 92, and the lowest score of 78 and with an average score of 86.5 final total score 2684. The results of the analysis obtained are t_ (count) (-15.183) < t_ (table) (2.042) Then H_ (a) can be accepted and H_ (o) is rejected. From the results of the study it can be concluded that there is an effect of drill method training on the front roll ability of class VIII students at SMP Negeri 18 Bengkulu City.